Poles, Germans and Americans in the Light of Interphilosophical Comparative Studies - Andrzejewski, Bolesław (Sensus Historiae, 2022)
The aim of the article is to show three philosophical systems: Polish practicism, German rationalism and American pragmatism. They are compared in terms of interphilosophy. The main topic is the Polish mentality, described in its essence and in its historical evolution, but also in its connections to two other mentalities. In this way, the “Polish humanism” arises out of three threads.